What Determines Global Flows of Entrepreneurial Finance? - Hall, Thomas (Journal of Accounting and Finance, 2024)
Economists examine foreign direct investment, which mostly constitutes flows to established firms (sometimes characterized as “multinational corporations”) that might or might not engage in truly innovative activity in the FDI target country. Conversely, finance scholars have studied the pipeline of entrepreneurial finance from limited partnerships (LPs) to venture capitalists (VCs) or private equity general partners (GPs) to portfolio firms. Few studies examine relationships between general and limited partners, and those that do often examine only the United States, or a limited number of countries in a given region. This paper uses a novel dataset (LP Source) to examine secular trends in cross-national flows from the LP to the GP (in the form of various investment funds) to the portfolio firm. We find evidence for “home bias” and demonstrate that cross-border flows are affected by GDP per capita, export orientation, and country-level measures of the entrepreneurial environment.